The Features of Theatrical Life in Hungary: The Legal and Financial Basis - Romanova, Olga; Khaunina, Ekaterina (Slavica, 2018)
The present study is concerned with the Hungarian theatre system. In the first part general questions connected with the existing model of theatrical activity are treated. This is followed by an analytical review of modern Hungarian cultural legislation, in which special attention is paid to the structure and content of Law XCIX / 2008 “On the support and rules of employment in organizations of performing arts”. Then all the existing present-day models of direct and indirect financial support of theatrical organizations are considered. Since the Hungarian and Russian theatre systems have some similar characteristics, the final part is devoted to possible partial adoption of Hungarian experience with a view to developing the institutions for the additional funding of Russian theatres.